Incorporation of a polymerization catalyst for improved mechanical behavior and physicochemical characteristics of a light-cured pulp capping material - Viviane Andrade Dias, Jéssyka; Virgínia de Freitas Chaves , Letícia; Xavier de Sousa-Lima, Rodolfo; Castillo Dutra Borges, Boniek (Brazilian Dental Science, 2022)
Objective: To evaluate the influence of the incorporation of a polymerization catalyst to a light-cured pulp capping material on mechanical behavior and physicochemical characteristics. Material and Methods: Different percentages (2 wt%, and 4 wt%) of diphenyliodonium hexafluorophosphate (DPI) were incorporated into the Ultra-Blend Plus, a resin-modified calcium-based cement. The material without incorporation of DPI (0 wt%) served as control. Degree of Conversion (DC), Flexural Strength (FS), Elastic Modulus (EM), Water Sorption (WSp), Solubility (Sl), and pH of eluate at 24-h, 72-h, and 7-day storage times were measured. One-way ANOVA/ Tukey posthoc tests were used to analyze the data (p <0.05). Results: For DC, FS, and EM, materials with different % of DPI showed statistically significant differences, so that 0% provided the lowest values and 2% the highest values. Materials with 0% and 2% of DPI provided statistically the lowest WSp, whilst material with 0% of DPI showed statistically the highest Sl. Conclusion: All materials provided statistically similar pH to eluates regardless of storage time, although only materials with DPI at 2% and 4% maintained pH of eluates statistically similar from 72 h to 7 days storage times. KEYWORDS Light-cured pulp capping material; Polymerization catalyst; Pulp capping.